Response of Abies spectabilis from the treeline ecotone to climate change in Mustang region of Nepal Himalayas - Gaire, Narayan Prasad; Dhakal, Yub Raj; Ghimire, Shravan; Bhandari, Sanjaya; Poudel, Srijan; Shah, Santosh K. (FORESTRY: Journal of Institute of Forestry, Nepal, 2025)
Alpine treelines serve as a sensitive bio-monitor and an early warning indicator of climate change impacts on high-altitude ecosystems. We conducted a dendrochronological study in the treeline ecotones in the Mustang region, Annapurna Conservation Area, Nepal, to assess the effects of climate change on Abies spectabilis (D. Don) Mirb. We collected tree core samples from 40 trees and analysed them, using the standard dendrochronological procedure. We developed a 97-year tree-ring width chronology spanning from 1919 to 2015, which demonstrates strong dendroclimatic potential. The sampled trees had an average annual radial growth of 0.37 ± 0.74 mm/yr and a mean age of 43.1 years. The basal area increment (BAI) chronology of this species in this region indicates a slight decline in its growth in recent years. Moisture availability during the growing season primarily controls the growth of A. spectabilis, as indicated by its negative relationship with summer maximum temperature and positive relationship with precipitation. A higher winter maximum temperature also positively favoured the growth in the following growing season. These climatic influences have shifted over time, with increasingly negative relationships with June and August temperatures and a weakened positive relationship with July temperatures, while the positive influence of August precipitation remains stable. The projected increases in drought frequency and severity under ongoing global warming are likely to adversely affect the growth of A. spectabilis at high‑elevation treelines.